Impact of goodwill on firms’ capital structure in developing countries - Thakur, Oli Ahad; Amin Noordin, Bany Ariffin; Tunde, Matemilola Bolaji; Razman, Ahmed; Satiawan, Doddy (Rajshahi, 2020)
Goodwill assets are considered to be a building block to reduce some concerns surrounding the capital structure puzzle. This article investigates goodwill assets as a determinant of firms' capital structure using 4912 listed firms from 23 developing countries. This article applies the two-step system GMM as the main estimation technique because it mitigates the endogeneity problem. Moreover, it applies the Fixed Effect and Random Effect models as robust checks. The results show that goodwill assets are significantly and positively related to firms' capital structure in the two-step system GMM model as well as in the Fixed Effect and Random Effect models. Based on these results, goodwill assets emerge as a potential determinant of capital structure, which implies that goodwill assets could serve as collateral to obtain debt capital.